2019
DOI: 10.1039/c9ta01332f
|View full text |Cite
|
Sign up to set email alerts
|

Mass production of graphene materials from solid carbon sources using a molecular cracking and welding method

Abstract: A novel process is developed for high-volume production of low-cost graphene materials from any solid carbon resources, especially biomass sources. Few-layer graphene materials from solid carbon resources are produced through a molecular cracking and welding (MCW) method. The MCW technique is a single step process with two stages, i.e., graphene-encapsulated core-shell nanoparticles are first formed by catalytic thermal treatment of solid carbon materials. Then in the second stage these core-shell structures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…Structurally, graphene is free of defects, with all the carbon atoms linked together by strong and flexible bonds. This has made graphene to have outstanding properties such as electronic, optical, mechanical, and thermal properties (Yan et al 2019) as shown in Table 2. The former 3D allotropes have been studied for many years ago, whereas fullerenes and nanotubes have been only discovered and studied lately.…”
Section: Synthesis Of 3d Multifunctional Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structurally, graphene is free of defects, with all the carbon atoms linked together by strong and flexible bonds. This has made graphene to have outstanding properties such as electronic, optical, mechanical, and thermal properties (Yan et al 2019) as shown in Table 2. The former 3D allotropes have been studied for many years ago, whereas fullerenes and nanotubes have been only discovered and studied lately.…”
Section: Synthesis Of 3d Multifunctional Hybridsmentioning
confidence: 99%
“…It is an attractive electrode material for electrochemical capacitors (ECs) because of its unique atom-thick 2D structure and excellent properties such as high electron mobility, high electrical conductivity, large specific surface area, good electrochemical stability, and/or processability (Yan et al 2019;Chae and Lee 2014;Bhuyan et al 2016;Wu et al 2012;Lee et al 2019). Graphene is extraordinarily strong (the strongest material ever known or tested), supernaturally light, and electrically superconductive.…”
Section: Synthesis Of 3d Multifunctional Hybridsmentioning
confidence: 99%
“…To massively manufacture low-priced graphene materials, a molecular cracking and welding (MCW) method has been developed for producing few-layer graphene from solid carbon resources, especially biomass sources [ 1 , 2 ]: graphene-encapsulated transitional metal nanostructures are first produced by graphitization of mixtures of metal catalyst and solid carbon materials. Then, graphene-encapsulated transitional metal structures are cracked by ‘scissoring molecules’, and the cracked few-layer graphene shells are peeled off the metal cores to serve as building block units for self-welding and reconstructed into high-quality, few-layer graphene materials under the heating temperature with selected welding reagent gases [ 1 , 2 ]. According to the MCW concept, graphene-encapsulated core–shell nanoparticles are first prepared by catalytic graphitization of solid carbon resources [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, graphene-encapsulated transitional metal structures are cracked by ‘scissoring molecules’, and the cracked few-layer graphene shells are peeled off the metal cores to serve as building block units for self-welding and reconstructed into high-quality, few-layer graphene materials under the heating temperature with selected welding reagent gases [ 1 , 2 ]. According to the MCW concept, graphene-encapsulated core–shell nanoparticles are first prepared by catalytic graphitization of solid carbon resources [ 1 , 3 ]. To obtain good catalytic effect, a uniform catalyst-solid carbon mixture must be made [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…29 The hydrophobic lightweight graphene structures can rapidly absorb oil phase from water, with a capacity up to over 100 times their own weight in oil. 30 The oil can be easily drained from the 3DGNs, so these absorbents can be reused for many times. 31 Currently, most of the 3DGNs are made from graphene oxide or graphite-derived graphene, which make 3DGN materials expensive and significantly slow down their potential usage in high volume applications.…”
Section: Introductionmentioning
confidence: 99%